1998
DOI: 10.1046/j.1365-3083.1998.00315.x
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of B7‐2, Not B7‐1, Inhibits Purified Protein Derivative‐Primed T‐Lymphocyte Responses But Fails to Influence the Proportion of Th1 Versus Th2 Subsets

Abstract: The ability to select for a cell-mediated response rather than antibody production following infection with intracellular mycobacteria, would be an advantage in preventing the occurrence of disease. Recent work suggests that the two members of the B7 family of costimulatory molecules, B7-1 and B7-2, may differentially influence the nature of primary immune responses but little is known of their role in this capacity in secondary responses. We have used an in vitro model to investigate whether blocking B7-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(26 reference statements)
1
2
0
Order By: Relevance
“…The results from these in vivo studies are consistent with the in vitro observations reported earlier from our laboratory, that treatment with rgpTNF‐α of spleen cells from BCG‐vaccinated guinea pigs enhanced the T cell proliferation to PPD and not ConA [21]. The differential effect of TNF‐α on PPD or ConA‐induced T cell proliferation may be attributed to the differential contributions of co‐stimulation by antigen‐presenting cells (APC), as reported by others [36,37]. From our study, as well as from others, it is clear that TNF‐α causes further proliferation of T cells but TNF blockade enhances both Th1 (IFN‐γ and IL‐12p40) and Th2 (IL‐10) cytokine responses in mice with chronic tuberculosis infection [13,21].…”
Section: Discussionsupporting
confidence: 92%
“…The results from these in vivo studies are consistent with the in vitro observations reported earlier from our laboratory, that treatment with rgpTNF‐α of spleen cells from BCG‐vaccinated guinea pigs enhanced the T cell proliferation to PPD and not ConA [21]. The differential effect of TNF‐α on PPD or ConA‐induced T cell proliferation may be attributed to the differential contributions of co‐stimulation by antigen‐presenting cells (APC), as reported by others [36,37]. From our study, as well as from others, it is clear that TNF‐α causes further proliferation of T cells but TNF blockade enhances both Th1 (IFN‐γ and IL‐12p40) and Th2 (IL‐10) cytokine responses in mice with chronic tuberculosis infection [13,21].…”
Section: Discussionsupporting
confidence: 92%
“…The above results show that BCG‐infected DC are able to stimulate naïve T cells to proliferate more strongly than TNF‐α‐exposed DC. This could be because of presentation of antigens from BCG onto MHC class I and MHC class II, 16–18 or increased levels of co‐stimulatory molecules or cytokine secretion 19 . It is beyond the scope of this paper to address whether the T‐cell activation and proliferation is a result of presentation of BCG antigens on MHC class I and II or to increased T‐cell responses to self antigens that are presented on these more ‘mature’ DC.…”
Section: Discussionmentioning
confidence: 99%
“…This could be because of presentation of antigens from BCG onto MHC class I and MHC class II, [16][17][18] or increased levels of costimulatory molecules or cytokine secretion. 19 It is beyond the scope of this paper to address whether the T-cell activation and proliferation is a result of presentation of BCG antigens on MHC class I and II or to increased T-cell responses to self Figure 5. Autologous peripheral blood lymphocytes were co-cultured with media (&), media-exposed DC (*), TNF-a-exposed DC (&), or BCG-exposed DC (~) for 24-96 hr.…”
Section: Discussionmentioning
confidence: 99%